Developing in-service science teachers’ ownership of the PROFILES pedagogical framework through a technologysupported participatory design approach to professional development - Kyza, Eleni A.; Georgiou, Yiannis (My University, 2014)
Teacher ownership is crucial for the sustainability of science education reform efforts. This paper discusses participatory design as a bottom-up approach for promoting teachers’ sense of ownership of inquiry-based learning and teaching approach as put forward by the PROFILES project. According to the prevalent argument in favor of participatory design, this approach leads to designs that are ecologically valid and attuned to different stakeholder needs. In this study, we report on the investigation of a technologically-mediated approach of participatory design of inquiry-based learning. Research questions address the teachers’ perceptions of the affordances and trade-offs of the participatory design approach, and its effect on teacher design efforts and on student motivation. We collected qualitative data from 26 teachers and quantitative data from 171 high school students. Teachers reported that the process of collaborative design and the enactment of the designed module increased their ownership towards the PROFILES module. The analysis of nine chemistry teachers’ discourse revealed that this process allowed them to collaborate productively, resulting in the development of a module that adopted the PROFILES 3-stage philosophy and was more aligned with their students’ needs. The analysis of students’ surveys indicated a statistically significant increase in motivation. These findings suggest that technologically-mediated participatory design is a valid approach for promoting teacher ownership of the PROFILES approach in science teaching.
Keywords: Participatory design; Teacher ownership; Technology-supported professional development; Science education; PROFILES